Fever in children: parents' search for urgent and emergency services - Pitoli, Pedro Jose; Duarte, Brenda Katheryne; Fragoso, Andressa Amorim; Damaceno, Daniela Garcia [UNESP]; Sanches Marin, Maria Jose (Abrasco-assoc Brasileira Pos-graduacao & Saude Coletiva, 2021)
The study analyses the understanding of parents or guardians of children aged zero to five years old about fever, the conduct and care for this condition, carried out in the urgent and emergency service. The qualitative research, which used the thematic analysis technique, was carried out through interviews with 14 parents or guardians who sought an urgent and emergency Pediatric Service in a municipality in the countryside of Sao Paulo for this reason. The experiences of parents who seek these services are associated to three main topics: fear of fever; care for a febrile child; and the experience of care at the urgent and emergency services. It was identified that an exaggerated fear of fever predominates and that parents / guardians feel safe regarding the existing technology found in urgent and emergency services. The adopted precautions, however, are not always those recommended for the existing situation.
Keywords: Child health; Fever; Child care; Parents; Emergency medical service